Comparative transcriptome profiling of resistant and susceptible rice genotypes in response to the seedborne pathogen Fusarium fujikuroi. (December 2016) - Matić, Slavica; Bagnaresi, Paolo; Biselli, Chiara; Orru', Luigi; Amaral Carneiro, Greice; Siciliano, Ilenia; Valé, Giampiero; Gullino, Maria; Spadaro, Davide
Abstract Background Fusarium fujikuroi is the causal agent of bakanae, the most significant seed-borne disease of rice. Molecular mechanisms regulating defence responses of rice towards this fungus are not yet fully known. To identify transcriptional mechanisms underpinning rice resistance, a RNA-seq comparative transcriptome profiling was conducted on infected seedlings of selected rice genotypes at one and three weeks post germination (wpg). Results Twelve rice genotypes were screened against bakanae disease leading to the identification of Selenio and Dorella as the most resistant and susceptible cultivars, respectively. Transcriptional changes were more appreciable at 3 wpg, suggesting that this infection stage is essential to study the resistance mechanisms: 3, 119 DEGs were found in Selenio and 5, 095 in Dorella. PR1, germin-like proteins, glycoside hydrolases, MAP kinases, and WRKY transcriptional factors were up-regulated in the resistant genotype upon infection withF. fujikuroi . Up-regulation of chitinases and down-regulation of MAP kinases and WRKY transcriptional factors were observed in the susceptible genotype. Gene ontology (GO) enrichment analyses detected in Selenio GO terms specific to response toF. fujikuroi : 'response to chitin', 'jasmonic acid biosynthetic process', and 'plant-type hypersensitive response', while Dorella activated different mechanisms, such as 'response to salicylic acid stimulus' and 'gibberellin metabolic process', which was in agreement with the production of gibberellin A3 in Dorella plants. Conclusions RNA-seq profiling was performed for the first time to analyse response of rice toF. fujikuroi infection. Our findings allowed the identification of genes activated in one- and three- week-old rice seedlings of two genotypes infected withF. fujikuroi . Furthermore, we found the pathways involved in bakanae resistance, such as response to chitin, JA-dependent signalling and hypersensitive response. Collectively, this provides important information to elucidate the molecular and cellular processes occurring in rice duringF. fujikuroi infection and to develop bakanae resistant rice germplasm.